ANALYSIS OF THE POTENTIAL IMPACT OF SOCIAL MEDIA USAGE ON THE MENTAL HEALTH OF ADOLESCENTS - RIAZ , M; RIAZ , L (Biological and Clinical Sciences Research Journal, 2024)
The increasing prevalence of social media usage among adolescents has raised concerns about its potential impact on mental health. The interplay between social connectedness, self-esteem, and mental health requires further exploration to understand the mediatObjective:ing mechanisms involved. To assess the association between social media usage and adolescents’ mental health and the impact of social connectedness and self-esteem on this association. Methods: A cross-sectional study was conducted in the Department of Pediatrics and Department of Psychiatry of DHQ, Narowal from October 2022 to October 2024. A total of 500 adolescents aged from 12 to 15 years attending the hospital departments were included in the study. Data was collected by a 25-item self-completion Strengths and Difficulties questionnaire to assess mental disorders in the participants. To evaluate social media usage, participants were about time spent on its usage. Self-esteem and social interaction were also assessed as mediators. Results: In unadjusted analysis, participants with more active hours had poor mental health with a one-point increase in SDQ score with every increase in socialization (95% CI: 0.19-1.68). Unadjusted analysis showed that more hours on social media led to low self-esteem (p=0.01) and, hence poor mental health (p<0.001). The Monte Carlo test was also significant for an indirect association between self-esteem and mental health (p=0.02) with a 70% impact of social media mediated by self-esteem. More hours on social media were related to reduced happiness with friends (p=0.01) but this did not lead to poor mental health (p=0.58). Conclusion: A higher number of hours spent on social media leads to mental health problems in adolescents in the long term. Additionally, low self-esteem due to social comparison by the use of social media is also an indirect mediator of poor mental health.